A low-radiation exposure protocol for 3D QCT of the spine - Museyko, Oleg; Heinemann, A.; Krause, M.; Wulff, B.; Amling, M.; Pueschel, K.; Glueer, C. C.; Kalender, Willi Alfred; Engelke, Klaus (Osteoporosis international, 2014)
Cadaver and phantom measurements and simulations confirmed that radiation exposure in 3D QCT of the spine can be reduced if 80 kV instead of 120 kV protocols are used; 120 mAs and slice thicknesses of 1-1.3 mm should be usable but obese patient will require higher milliampere-second settings.To develop a low-radiation exposure CT acquisition protocol for 3D QCT of the thoracolumbar spine.Twenty-six cadavers were scanned with a standard protocol of 120 kV, 100 mAs and with a low-dose protocol using 90 kV, 150 mAs. The scan range included the vertebrae T6 to L4. Each vertebra was segmented and the integral volume and BMD of the total vertebral body were determined. Effective dose values were estimated. The impact of milliampere-second reduction on image quality was simulated by adding noise.One hundred ninety-six vertebrae were analyzed. Integral volume as well as integral BMD correlated significantly (p < 0.001) between standard and low-dose protocols (volume, r (2) = 0.991, residual root mean square (RMS) error, 0.77 cm(3); BMD, r (2) = 0.985, RMS error, 4.21 mg/cm(3)). The slope significantly differed from 1 for integral BMD but not for volume hinting at residual field inhomogeneity differences between the two voltage settings that could be corrected by cross-calibration. Compared to the standard protocol, effective dose was reduced by over 50 % in the low-dose protocol. Adding noise in the 90 kV images to simulate a reduction from 150 to 100 mAs did not affect the results for integral volume or BMD.For 3D QCT of the spine, depending on scanner type, 80 or 90 kV instead of 120 kV protocols may be considered as an important option to reduce radiation exposure; 120 mAs and slice thicknesses of 1-1.5 mm are usable if segmentation is robust to noise. In obese patients, higher milliampere-second settings will be required.
EVALuna2:10069